Unveiling the Art of Metaphor Translation Techniques in Eragon by Christopher Paolini - NoerSyafa'ah, Reza; Kuswahono, Deny; Priyambudi, Surya (EL2J (English Language and Literature Journal), 2024)
This study investigates the translation procedures used by Sendra B. Tanuwidjaya to convey metaphors from Christopher Paolini's “Eragon” novel into Indonesian. Based on George Lakoff's metaphor theory and Hurtado Albir's translation theory, it identifies 139 metaphors that are classified as structural (77), orientational (15), and ontological (47). Using a descriptive qualitative method, the research focuses on the translator's use of strategies such as literal translation, modulation, and modification to balance the original's tone and style with cultural relevance for Indonesian readers. The findings highlight the significance of nuanced tactics in literary translation and encourage additional research into the difficulties of metaphor translation.